Piecemeal Planning and Small-Town Development In Mlandizi and Sirari, Tanzania (Tanzania Journal for Population studies and Development, 2022)
Urbanization is vivid in big urban centres as well as in small and emerging urban centres, thus causing pressure on planning professionals to provide minimum planning solutions for guiding spatial development. As a result, in Tanzania, small towns are planned piecemeal, regardless of the fact that the practice is contrary to planning policy in countries that have adopted the master planning approach. This article examines the implications of piecemeal planning in guiding spatial development in Mlandizi and Sirari, which are small towns in Tanzania. Data were obtained through in-depth interviews, field observation and spatial mapping using the Geographical Information System (GIS). Thematic and spatial analyses were conducted to ascertain the practice, process and implication of piecemeal planning. The findings show that Mlandizi and Sirari towns are characterized by rapid informal urbanization, while planning is done piecemeal. Town planners’ adoption of piecemeal planning is influenced by local realities evidenced by structural challenges associated with the adoption of neo-liberal planning policies in the context of low institutional capacity on the part of local government authorities. While the approval of piecemeal plans by the governments at the local and central levels legitimises the practice, piecemeal planning has resulted in uncoordinated urban spatial structures and urban sprawl. Thus, it is recommended that regulations be instituted through the preparation of structure plans to guide piecemeal planning.